Bacteriophage-encoded lethal membrane disruptors: Advances in understanding and potential applications - Abeysekera, Gayan S.; Love, Michael J.; Manners, Sarah H.; Billington, Craig; Dobson, Renwick C. J. (Frontiers in Microbiology, 2022)
Holins and spanins are bacteriophage-encoded membrane proteins that control bacterial cell lysis in the final stage of the bacteriophage reproductive cycle. Due to their efficient mechanisms for lethal membrane disruption, these proteins are gaining interest in many fields, including the medical, food, biotechnological, and pharmaceutical fields. However, investigating these lethal proteins is challenging due to their toxicity in bacterial expression systems and the resultant low protein yields have hindered their analysis compared to other cell lytic proteins. Therefore, the structural and dynamic properties of holins and spanins in their native environment are not well-understood. In this article we describe recent advances in the classification, purification, and analysis of holin and spanin proteins, which are beginning to overcome the technical barriers to understanding these lethal membrane disrupting proteins, and through this, unlock many potential biotechnological applications.